The moderating effect of an audit committee on the relationship between ownership structure and firm performance: Evidence from emerging markets - Waleed M. Al-Ahdal; Hafiza Aishah Hashim; Faozi A. Almaqtari; Shahrokh M. Saudagaran (Cogent Business & Management, 2023)
The study aims to investigate the relationship between ownership structure (OS) and financial performance (FP) in non-financial listed companies operating in Oman and the UAE, using panel data from 2012 to 2021. The results revealed that Tobin's Q (TQ) is positively and significantly affected by managerial ownership and family ownership. In addition, return on asset (ROA) is found to have a negative and significant relationship with managerial ownership, while return on equity (ROE) is found to have a positive and significant relationship with family ownership. Comparing Oman and the UAE, the results indicated that all ownership variables tested have superior influence on FP. This study also documented that the moderating effect of the audit committee has a more positive relationship between managerial ownership, ownership concentration, and family ownership on firm performance in both countries. This study fills existing gaps in contemporary literature on OS in emerging markets by dissecting the outcome of OS on FP of companies in Oman and the UAE. To the best of our knowledge, most of the prior studies on OS have not examined the moderating effect of audit committee on the relationship between OS and FP. Our study on the OS in Oman and UAE listed firms shows that OS have an important outcome on market-based calculation. This study expands our understanding of the impact of OS on FP in emerging markets in two countries in the Gulf Cooperation Council (GCC), a region of growing economic importance that has not received adequate research attention.
Keywords: 650; Financial Performance (FP); Gulf Cooperation Council (GCC); Oman; Ownership Structure (OS); UAE